Which Reputations Does a Brand Owner Need? Evidence from Trade Mark Opposition - Georg von Graevenitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
At least two: the reputation of their brand and a reputation for being tough on imitators of this brand. Sustaining a brand requires both investment in its reputation amongst consumers and the defence of the brand against followers that infringe upon it. I study the defence of trade marks through opposition at a trade mark office. A structural model of opposition and adjudication of trade mark disputes is presented. This is applied to trade mark opposition in Europe. Results show that brand owners can benefit from a reputation for tough opposition to trade mark applications. Such a reputation induces applicants to settle trade mark opposition cases more readily.
urn:nbn:de:bvb:19-epub-13337-1
Keywords: K41; L00; O31; O34; 330; trade marks; opposition; intellectual property rights; reputation